A Perspective Review on Numerical Simulations of Hemodynamics in Aortic Dissection - Wan Naimah Wan Ab Naim; Poo Balan Ganesan; Zhonghua Sun; Kok Han Chee; Shahrul Amry Hashim; Einly Lim (The Scientific World Journal)
Aortic dissection, characterized by separation of the layers of the aortic wall, poses a significant challenge for clinicians. While type A aortic dissection patients are normally managed using surgical treatment, optimal treatment strategy for type B aortic dissection remains controversial and requires further evaluation. Although aortic diameter measured by CT angiography has been clinically used as a guideline to predict dilation in aortic dissection, hemodynamic parameters (e.g., pressure and wall shear stress), geometrical factors, and composition of the aorta wall are known to substantially affect disease progression. Due to the limitations of cardiac imaging modalities, numerical simulations have been widely used for the prediction of disease progression and therapeutic outcomes, by providing detailed insights into the hemodynamics. This paper presents a comprehensive review of the existing numerical models developed to investigate reasons behind tear initiation and progression, as well as the effectiveness of various treatment strategies, particularly the stent graft treatment.